Comparative Phytochemical Profile of Some Medicinal Plants from Gilgit-Baltistan - Ismail, Muhammad; Jamal, Shams; Haq, Noor Ul; Hussain, Shabbir; Hussain, Shafqat (Progress in Nutrition, 2020)
The aim of this study was to evaluate the presence of phytochemicals like alkaloids, flavonoid, tannins, saponnins, phenols, quinones, steroids, and sterols in five different medicinal plants collected from Gilgit region of Pakistan. The plants were Daphne mucronata (Dm), Punica granatum (Pg), Kochia prostrata (Kp), Isodon rugosus (Ir), and Pistacia khinjuk (Pk). The plants were first dried at room temperature and grounded to powder form. The powder was placed for soaking into methanol for ten days. The methanolic extract was further fractionated by using n-hexanes, dichloromethane, and water through solvent-solvent extraction. These extracts were further treated with different reagent to check the presence of different phytochemicals these plant species. The results showed that all the five plants contain phytochemical constituents like alkaloid, flavonoid, steroids, and tannins. Phenols were absent in hexane and dichloromethane (DCM) extracts of Dm, Pg, Ir, and Pk. Similarly, steroids and sterols were not present in hexane and DCM extracts of Dm, quinones was absent in Pg and Pk, and saponins in Ir. The water extract of all plants showed good results, followed by DCM extracts. The hexanes extracts showed poor results for all phytochemicals with different reagents.